Comparative Analysis of Two-Coil and Three-Coil Structures for Wireless Power Transfer - Zhang, Jian; Yuan, Xinmei; Wang, Chuang; He, Yang (IEEE transactions on power electronics, 2017)
With the development of electric vehicles and consumer electronics, wireless power transfer (WPT) is becoming a popular technology. Recently, magnetic resonant coupling has been considered to be the most effective and attractive WPT approach, and the two-coil structure is the most widely used for magnetic resonant coupling. It has been recently reported that the system's energy efficiency can be improved by a three-coil structure. In this paper, the three-coil structure is compared with the two-coil structure based on circuit theory. Simplified circuit models of the two- and three-coil structures are proposed to give a more intuitive and comprehensive analysis of the energy efficiency differences between the two structures. With the simplified model, the condition for a three-coil structure obtaining higher energy efficiency over its two-coil counterpart is derived, and the analysis shows that the WPT system with higher energy efficiency within a wider range of loads can be achieved by properly designed three-coil systems. Additionally, it also shows that the three-coil system has the significant advantage of reducing the current stress and the electromagnetic field emission that is caused by misalignments. The theoretical analysis is confirmed by both simulation and experimental results.